Cytomegalovirus and other herpesviruses infections in heart and bone marrow transplant recipients - Weinberg, Adriana; Vilas Boas, Lucy S.; Feher, Olavo; Strabelli, Tania M. V.; Fink, Maria Cristina D. S.; Dulley, Frederico L.; Uip, David E.; Bellotti, Giovani; Chamone, Dalton A. F.; Amato Neto, Vicente; Pannuti, Cláudio S. (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
From January 1988 to January 1989 all the heart transplant and bone marrow recipients at the Instituto do Coração of the Hospital das Clínicas of the University of São Paulo Medical School were studied for the incidence and morbidity associated with herpesviruses infections after transplantation. Five bone marrow and 5 heart transplant recipients were followed for a mean of 4.2 months post-transplantation. All the patients were seropositive for cytomegalovirus (CMV) before admission and 80% experienced one or more recurrences during the observation period. Of the 12 episodes of CMV infection, that were identified in this study, 83% were accompanied by clinical or laboratory abnormalities. However, there was only one case of severe disease. The overall incidence of infection for herpes simplex (HSV) was 50%. Although most of HSV reactivations were oral or genital, one case of HSV hepatitis occurred. One of the 6 episodes of HSV infections that were treated with acyclovir showed an unsatisfactory response and was successfully managed with ganciclovir. All the individuals had anti-varicella zoster virus antibodies, but none of them developed infection. The study emphasizes the importance of active diagnostic surveillance of herpesvirus infections in transplant patients. Both CMV and HSV reactivations showed high incidence and important morbidity and thus, deserve prophylactic therapy.